"I voice out because I care": the effect of online social networking on employees' likelihood to voice and retention. Issue 1 (13th November 2020) - Mohammad, Jihad; Quoquab, Farzana; Sulaiman, Ahmad Nuruddin; Abdul Salam, Zarina
Abstract : Purpose: This study aims to examine the mediating role of "employees' likelihood to voice (ELTV)" in the relationship between "online social networking (OSN)" and "employee retention (ER)" and to predict the effect of OSN on ELTV and ER. Design/methodology/approach: A cross-sectional study using the survey method was employed to collect data from 251 administrative staff of the healthcare industry. The partial least squares (PLS) technique, using SmartPLS3 software, was employed to test the study hypotheses. Findings: The results of this study supported the direct effect of OSN on ELTV and ER. Moreover, the mediating effect of ELTV was also supported by the data. Originality/value: This study provides new knowledge about the direct and indirect effects of OSN on ELTV and ER.